Silent sinus syndrome: combined sinus surgery and orbital reconstruction – report of 15 cases. (2nd January 2019) - Clarós, Pedro; Sobolewska, Aleksandra Zofia; Cardesa, Antonio; Lopez-Fortuny, Marta; Claros, Andres
Abstract: Background: Silent sinus syndrome (SSS) is defined as spontaneous, painless enophthalmos, hypoglobus with orbital floor resorption and maxillary sinus collapse on the ipsilateral side. Different methods of orbital floor reconstruction have been proposed. Aims/objectives: The purpose was to analyse the results of combined endoscopic sinus surgery (ESS) and reconstruction using orbital floor implant of 15 patients with SSS and to present recent histological findings. Materials and methods: Retrospective case review of 15 patients with SSS treated in clinic between 2007 and 2017. Results: Eleven women and four men presented with unilateral, spontaneous enophthalmos. Averaged duration of enophthalmos was 10.7 months. On affected side, mean enophthalmos was 2.6 mm and hypoglobus 2.7 mm. Computed tomography imaging (CT) imaging showed maxillary sinus opacification on the affected side in every case, and the orbital floor was displaced downwards in all cases. In total, 13 patients underwent simultaneous ESS and rebuilding of orbital floor with a titanium implant. Statistical analysis confirmed significant differences for pre- and postoperative measure of enophthalmos and hypoglobus. Conclusion and significance: Implementation of titanium implants is the reliable method of reconstruction that allows good aesthetic result, shorter time of procedure with an excellent long-term outcome and satisfactory patient's tolerance.